2018
DOI: 10.1038/s41385-018-0070-z
|View full text |Cite
|
Sign up to set email alerts
|

Dietary DHA amplifies LXA4 circuits in tissues and lymph node PMN and is protective in immune-driven dry eye disease

Abstract: Recently identified regulatory PMN control immune-driven dry eye disease (DED) in females by producing the arachidonic acid (ω-6)-derived specialized pro-resolving mediator (SPM), LXA, in lymph nodes. Dietary ω-3 docosahexaenoic acid (DHA) is protective in DED but mechanisms of action remain elusive. DHA is converted to ω-3 SPMs by PMN via the same lipoxygenases (LOX) that generate LXA. We investigated if dietary DHA amplifies SPM formation and affects T effector cell function and/or regulatory PMN in DED. DED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 48 publications
3
28
0
Order By: Relevance
“…One possibility is that the higher gene activation of alox15 in the TG of the female mouse allows the synthesis of docosanoids to enhance the nerve regeneration. This suggestion is supported by previous studies that showed the benefit of lipoxin A 4 , a 15-LOX-related derivative of arachidonic acid for female mice in the immune-driven dry eye model (43, 44). Moreover, alox15 was shown to be a shared activated gene between the 3 mouse strains.…”
Section: Discussionsupporting
confidence: 78%
“…One possibility is that the higher gene activation of alox15 in the TG of the female mouse allows the synthesis of docosanoids to enhance the nerve regeneration. This suggestion is supported by previous studies that showed the benefit of lipoxin A 4 , a 15-LOX-related derivative of arachidonic acid for female mice in the immune-driven dry eye model (43, 44). Moreover, alox15 was shown to be a shared activated gene between the 3 mouse strains.…”
Section: Discussionsupporting
confidence: 78%
“…Consequently, restoration or supplementation of LX signaling may also present promising therapeutic potential, as they induce a proresolving effect in models of neuroinflammation, while also exerting direct neuroprotective activity. Recent interesting evidence suggests that dietary supplementation of omega‐3 PUFA can sustain the levels of SPMs in AD patients and amplifies LXA 4 levels in several tissues in mice …”
Section: Discussionmentioning
confidence: 99%
“…However, changes in AA or linoleic acid dietary intake can alter formation of other pro‐inflammatory metabolites, such as leukotrienes and prostaglandins . We have also recently shown that dietary changes in omega‐6 and omega‐3 PUFA intake can alter enzymatic LX production in the contexts of parenteral nutrition and ocular inflammation …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have uncovered the important roles of endogenous and tissue resident LXA 4 circuits on T cell function. The immune regulatory function of LXA 4 on cells was investigated in vivo in an immune-driven dry eye model, where neutrophil-derived LXA 4 was a critical resident signal to control pathogenic T helper cell type 1 (Th1) and T helper cell type 17 (Th17) effector cells and increased the number of T regulatory cells (Tregs) in the eye draining lymph nodes [11,12]. More importantly, sex-specific regulation of the LXA 4 circuit in resident lymph nodes was identified as a key factor that drives femalespecific immune-driven dry eye disease.…”
Section: Lxa 4 Regulation Of Lymphoid-derived Cellsmentioning
confidence: 99%
“…Recent reports have demonstrated that lipoxins are not only formed during inflammation and the resolution phase of inflammation, but that they are also part of normal signaling in healthy tissues and actively regulate homeostasis and the threshold for activation of immune responses in the cornea, lymph nodes, lacrimal glands and retina [11,12,19,20]. Regulation and therapeutic amplification of this homeostatic SPM circuit in health and diseases is the focus of several NIH-funded projects.…”
Section: Lxa 4 Regulation Of Lymphoid-derived Cellsmentioning
confidence: 99%